Ammonia Volatilization from Malaysian Soils Following Application of Urea - Yusop, Mohd Khanif (1992)
Surface application of urea often results in high ammonia volatilization loss. Information on ammonia volatilization in tropical acid soils is limited. This study was carried out to determine ammonia volatilization loss from surface applied urea in Malaysian soils and to study the ejects of soil properties on the rate of loss. Measurement of urease activity and ammonia volatilization loss in the laboratory was carried out on topsoil (0-15 cm) of 22 soils commonly found in Malaysia using a force-draft technique. Ammonia volatilization loss was recorded daily for seven days. Ammonia volatilization loss from the 22 soils studied ranged from 0.5 to 53% of N applied with most soils having values around 35 %. The ammonia loss in acid sulfate soil was low. Most of the loss occurred during the first 34 days after urea application. The urease acitivity of soils ranged from 12.20 to 150.50 uglg Nih and was not affected by soil texture and C content. Urease acitivity had a significant e1Ject on ammonia volatilization loss